Use of Cobra External Fixator for treatment of Distal Radius Fractures - Ranjeet, Niraj; Onta, Pratyenta Raj; Sapkota, Krishna; Thapa, Pabin; Wahegoankar, Krishna; Thapa, Upendra Jung (Asian Journal of Medical Sciences, 2018)
Background: Distal radius fractures are one of the commonest injuries only after clavicle fractures. These fractures poses challenges to the treating surgeons as a result of which these fractures are sometime treated unacceptably and leads to poor outcome. Among various treatment options for these fractures wrist sparing Cobra external fixator is one of the options with an impressive stability and outstanding functional outcomes. Aims and Objectives: To determine whether this system can achieve adequate reduction of a variety of DRF, is able to maintain reduction despite hand and wrist movements, whether it compromises hand and wrist functions and leads to long term problems. Materials and Methods: From July 1, 2016 - June 30, 2017, all skeletally matured patients with acute distal radius fractures (AO-A2, B1, C1, C2) were adequately reduced and fixed with Cobra ex-fix. Immediately post-op patients were encouraged to start range of motion of the wrist as the pain decreased. The patients were followed up in 2,4 and 8 weeks and were analyzed clinically, radiologically, their functional outcomes and any complications. Results: Twenty-two patients were included in our study. Nine were males and 13 were females. Using the AO classification, 15 were classified as A2, 2 were B1, 3 were C1, and 2 were C2. The mean number of weeks the cobra fixator was maintained was 5.3 weeks. The Cobra ex-fix was able to achieve excellent maintenance of radial height and radial inclination and good maintenance of dorsal tilt. Recovery of functional activities according to Gartland and Werley’s functional scoring system was good to excellent in all patients at 8 weeks follow-up. Conclusion: The Cobra external fixation system is an outstanding device for use in fractures of the distal radius. It achieves superior anatomic correction and is dependable in maintaining fracture reduction even with hand and wrist use. Asian Journal of Medical Sciences Vol.9(6) 2018 84-89